A Educação matemática & ensino médio: um panorama das pesquisas produzidas na PUC/SP - Oliveira, Eliane Alcântara de (2003)
The aim of this dissertation is to describe, analyse and categorize, according to the objective and research methodology, the dissertations on the Mathematics Education of the Secondary Level, produced at the PUC/SP Mathematics Education Postgraduation Program, from 1994 to 2000, based on, for that, the whole reading, filing and analysis of each document. The analysis consisted of finding out at each dissertation, evidences of the execution of research typical activities. The obtained results point out to the conclusion that most of those researchs, seven, aimed to benefit the construction of the function concept by the secondary level students, using for that the fulfillment of didatic sequences. The research methodology privileged by seven authors was the Didatic Engeneering and by the others three was the comparative analysis that showed to be efficient for the researchs development